2011
DOI: 10.1038/hdy.2011.118
|View full text |Cite
|
Sign up to set email alerts
|

Copy number polymorphism in the α-globin gene cluster of European rabbit (Oryctolagus cuniculus)

Abstract: Comparative genomic studies have revealed that mammals typically possess two or more tandemly duplicated copies of the a-globin (HBA) gene. The domestic rabbit represents an exception to this general rule, as this species was found to possess a single HBA gene. Previous electrophoretic surveys of HBA polymorphism in natural populations of the European rabbit (Oryctolagus cuniculus) revealed extensive geographic variation in the frequencies of three main electromorphs. The variation in frequency of two electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, the large population size increases the number of mutations (Bollback and Huelsenbeck, 2007;Peischl and Excoffier, 2015;Park et al,2019) which was also observed in EGS (117). We observed the highest levels of Sin EWR; the high value was consistent with Geraldes et al (2006) and Campos et al (2012). Tajima's D values were found to be significantly negative in EWR and EGS.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the large population size increases the number of mutations (Bollback and Huelsenbeck, 2007;Peischl and Excoffier, 2015;Park et al,2019) which was also observed in EGS (117). We observed the highest levels of Sin EWR; the high value was consistent with Geraldes et al (2006) and Campos et al (2012). Tajima's D values were found to be significantly negative in EWR and EGS.…”
Section: Discussionsupporting
confidence: 76%
“…Meanwhile, we recorded 286 mutations (ETA) in EWR. This was because EWR samples were collected from the hybrid zone in Iberian Peninsula in which Albacete is located (Campos et al, 2012). Furthermore, the large population size increases the number of mutations (Bollback and Huelsenbeck, 2007;Peischl and Excoffier, 2015;Park et al,2019) which was also observed in EGS (117).…”
Section: Discussionmentioning
confidence: 95%
“…Unfortunately this gene is not correctly assembled in the OryCun2.0 genome version and for this reason we could have missed it from our study even if it is still not clear if this variability is present only in wild rabbit populations or also in domesticated populations [42].…”
Section: Annotation Of Cnvrsmentioning
confidence: 92%
“…The high rate of gene duplication and loss in this family is likely mediated by unequal crossing-over and inactivation . Many of the gene duplicates within a species therefore have no 1:1 orthologues in other species (see, for example, Campos et al, 2012), and often have nearly identical sequence as the result of concerted evolution by means of interparalogue gene conversion . However, the a-globin genes of two rodents, the Norway rat (Rattus norvegicus) and the deer mouse (Peromyscus maniculatus), are a striking exception to this general pattern.…”
Section: Introductionmentioning
confidence: 99%